The political classroom evidence and ethics in democratic education - Hess, Diana E.; McAvoy, Paula (New York Routledge, 2015)
"never been agreement on what types of skills, dispositions, and knowledge ought to be taught, nor even agreement on how they should be taught. Grounded in thick empirical description and rich in ethical debate, The Political Classroom is the first book to focus on how democratic education is actually taught in real schools with real teachers and students. Based on one of the largest, mixed-methods studies of civic education ever undertaken, award-winning author Diana Hess and Paula McAvoy provide a systemic analysis of various approaches to teaching young people about democracy and democratic participation that exist in high schools throughout United States. By bringing the tools of social science and philosophy into conversation, this book engages readers in an examination of some persisting, important, and challenging dilemmas that are inherent in the process of educating young people to actively participate in political and civil society. Both clear and thoughtful in their presentation, Hess and McAvoy promote a coherent plan for improving the quality of classroom-based democratic education"--Publisher.
Keywords: Education -- Curricula -- Political aspects -- United States; Democracy and education -- United States; Academic freedom -- United States